Effects of tissue plasminogen activator timing on blood-brain barrier permeability and hemorrhagic transformation in rats with transient ischemic stroke - Zhang, Yanrong; Hoffmann, Angelika (Journal of the neurological sciences, 2014)
The goal of our study was to determine if the timing of the tissue plasminogen activator (tPA) administration influenced its effect on blood-brain barrier (BBB) permeability and the subsequent risk of hemorrhagic transformation. Thirty spontaneously hypertensive male rats were subjected to a 90-minute unilateral middle cerebral artery occlusion. Six rats did not receive tPA treatment (vehicle control: Group 0), intravenous tPA was administered immediately after reperfusion (Group 1) or 4h after reperfusion (Group 2). Dynamic contrast enhancement (DCE) and gradient-echo (GRE) MR sequences were used to assess the dynamic evolution of BBB permeability and hemorrhagic transformation changes at the following time points: during occlusion, and 3h, 6h, and 24h post reperfusion. In all groups, BBB permeability values in the ischemic tissue were low during occlusion. In Group 0, BBB permeability values increased at 3h after reperfusion (p=0.007, compared with the values during occlusion), and further at 6h after reperfusion (p=0.004, compared with those at 3h post reperfusion). At 24h post reperfusion, the values decreased to a level relative to but still higher than those during occlusion (p=0.025, compared with the values during occlusion). At 3h after reperfusion, BBB permeability values in the ischemic tissue increased, but to a greater extent in Group 1 than in Group 0 (p=0.034) and Group 2 (p=0.010). At 6h after reperfusion, BBB permeability values in the ischemic tissue increased further in Group 2 than in Group 0 (p=0.006) and Group 1 (p=0.001), while Group 1 exhibited BBB permeability that were still abnormal but less than those observed at 3h (p=0.001). Group 2 tended to have a higher hemorrhage incidence (36.4%, 4/11) than Group 1 (10.0%, 1/10, p=0.311) and Group 0 (0%), and hemorrhages occurred around 6h after reperfusion when BBB permeability values were the highest. Mortality was higher in Group 2 (63.6%, 7/11) than in Group 0 (0%) and Group 1 (10.0%, 1/10, p=0.024). The findings suggest that the timing of tPA administration is of importance for its impact on BBB permeability and subsequent risk of hemorrhagic transformation.